Respostas
respondido por:
5
= √6 (√2 + 1) - √2 (√3 - √6)
= √6.√2 + 1√6 - √2.√3 - √2 . (-√6)
= √12 + √6 - √6 + √12
= √12 + √12 +√6 - √6
= 2√12 + 0
= 2.√4.√3
= 2.2.√3
= 4 √3
Resp.: 4√3
***********************
12: 2
6: 2
3: 3
1 = 2.2.3 = 4.3 = √4.√3 = 2 √3
= √6.√2 + 1√6 - √2.√3 - √2 . (-√6)
= √12 + √6 - √6 + √12
= √12 + √12 +√6 - √6
= 2√12 + 0
= 2.√4.√3
= 2.2.√3
= 4 √3
Resp.: 4√3
***********************
12: 2
6: 2
3: 3
1 = 2.2.3 = 4.3 = √4.√3 = 2 √3
Perguntas similares
7 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás
10 anos atrás